Transformative Governance for the Future Navigating Profound Transitions - Caro-Gonzalez, Antonia (SpringerBriefs in Business, 2024)
This open access book helps actors who are committed to change unlock true innovative potential for the common good in their organizations. Innovation and change processes are not linear. Hence, this book presents a novel way to manage complexity. The author introduces readers to a comprehensive change management framework, the Eoh-for-Good blueprint methodology. It presents the method and discusses how it can be used to support collaboration, overcome challenges and achieve lasting changes in organizations with a 360-degree approach combining top-down, middle-round and bottom-up collaborative perspectives.